2004
DOI: 10.1308/003588404323043292
|View full text |Cite
|
Sign up to set email alerts
|

Pressure sores following elective total hip arthroplasty: pitfalls of misinterpretation

Abstract: On analysis, the data collection system was revealed to be flawed. Grade 1 areas (erythema with no ulceration) were included, leading to a dramatic discrepancy between reported and confirmed pressure sores. Re-analysis showed the confirmed pressure sore rates to be much lower (2.3% NHS, 1.0% private hospital). Conclusions: This audit suggests that both poor data collection and education lead to inaccurate audit. This may lead to subsequent inappropriate management and inappropriate NHS star ratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
1
6
0
3
Order By: Relevance
“…Considerando los datos de forma desglosada, tanto la incidencia en pacientes tras intervenciones de prótesis de cadera (27,8%) como tras intervenciones de prótesis de rodilla (15,4%) también resultan superiores a la mayoría de valores referidos por otros autores (15,21,22). Sólo algunos autores refieren cifras más elevadas, con una incidencia del 55% entre pacientes con fractura de cadera en Suecia (16), o una incidencia de 54,8%, tras cualquier intervención quirúrgica, en Turquía (27).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Considerando los datos de forma desglosada, tanto la incidencia en pacientes tras intervenciones de prótesis de cadera (27,8%) como tras intervenciones de prótesis de rodilla (15,4%) también resultan superiores a la mayoría de valores referidos por otros autores (15,21,22). Sólo algunos autores refieren cifras más elevadas, con una incidencia del 55% entre pacientes con fractura de cadera en Suecia (16), o una incidencia de 54,8%, tras cualquier intervención quirúrgica, en Turquía (27).…”
Section: Discussionunclassified
“…Por tanto, nuestros resultados confirman la estimación de una incidencia de UPP especialmente alta entre los pacientes sometidos a procedimientos quirúrgi-cos de cadera o rodilla (artroplastias y reparación de fracturas). Es conveniente tener presente que en este estudio se han contabilizado como UPP las lesiones de cualquier estadio, incluyendo el grado I (eritema que no blanquea), mientras que otros autores sólo consideran como UPP cuando se ha producido la ruptura de la integridad de la piel (grado II en adelante), lo cual puede introducir discrepancias en las cifras (22).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The scar contracture and bone exposure in one patient were caused by repeated drainage and infection of the sacral wound for 20 years after excision of a sacroiliac giant cell tumor. Three patients had bed sores with full-thickness skin loss with damage to subcutaneous tissue, not involving underlying fascia (Grade III using the criteria of Keong et al [9]) and three patients had sores with extensive destruction to muscle, bone, or supporting structure (Grade IV). The sizes of the sacral defects ranged from 10 cm 9 12 cm to 20 cm 9 25 cm (mean, 16 cm 9 20 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Keong et al compared the rates of pressure sore development after total hip replacement in two surgical units. 18 On analysis, it was found that grade 1 pressure sore areas (erythema with no ulceration) were included inappropriately for both units. Correct application of the definitions changed the results considerably (Table 1).…”
Section: Definitions Of Common Complicationsmentioning
confidence: 99%